2018
DOI: 10.18203/2320-6012.ijrms20181296
|View full text |Cite
|
Sign up to set email alerts
|

Teneligliptin add on to monotherapy treatment in patients with type 2 diabetes

Abstract: Background: In patient with type 2 diabetes (T2D) inadequately controlled on monotherapy, teneligliptin is efficacious and safe as add-on to treatment with oral antidiabetic drugs (OADs) or insulin. Data on efficacy of teneligliptin in Indian patients is relatively sparse. Aim of the study was to assess the efficacy of teneligliptin used as add-on treatment in patients inadequately controlled on monotherapy with OADs or insulin.Methods: We retrospectively evaluated the electronic database at our endocrinology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
3
1
0
Order By: Relevance
“…Between the two groups, HbA1c reduction is significant (P ≤ 0.01). The result was similar to those reported by other studies like Chatterjee, [15] Charbonnel et al, [16] Filozof and Gautier, [19] Muthukrishnan et al, [20] Kesavadev et al, [21] and Sahai et al [18] The current study used CEA, the cost comprised the direct costs involved in buying the drugs only . there was no adverse drug effect reported in any group, so additional cost for management of adverse effect is not included.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Between the two groups, HbA1c reduction is significant (P ≤ 0.01). The result was similar to those reported by other studies like Chatterjee, [15] Charbonnel et al, [16] Filozof and Gautier, [19] Muthukrishnan et al, [20] Kesavadev et al, [21] and Sahai et al [18] The current study used CEA, the cost comprised the direct costs involved in buying the drugs only . there was no adverse drug effect reported in any group, so additional cost for management of adverse effect is not included.…”
Section: Discussionsupporting
confidence: 90%
“…71.4 ± 21.4, compared to the intensification group, 52.7 ± 14.4. The result was similar to those reported by other studies like a study by Sarkar et al, [12] Chatterjee, [15] Gullapalli and Desai, [14] Jeon and Oh, [6] and Sahai et al [18] The primary goal of treatment is to target glycemic control by maintaining the HbA1C level near 6.5% to decrease the incidence of microvascular and macrovascular complications without predisposing study patients to hypoglycemia. It was observed that mean change in the reduction of HbA1c is more in the add on DPP4 group, i.e.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The effectiveness of teneligliptin in reducing glycemic burden as an add-on to monotherapy has been shown in various studies. A recent study conducted in India demonstrated patients with type 2 DM who had inadequate control of glycemic parameters with monotherapy, teneligliptin (20 mg/day) as add-on to existing treatment significantly reduced HbA1c, FPG, and PPG at 12 weeks, the same duration as that of current study implying again the potential efficacy of addition of teneligliptin on existing monotherapy on uncontrolled glycemic states of type 2 DM patients [22]. In another 16 weeks trial where teneligliptin was added at 20 mg/day to metformin showed a significant reduction in HbA1c (adjusted mean difference -0.90% vs. -0.12%, p<0.0001) and FPG (adjusted mean difference -1.10 mmol/L vs 0.15 mmol/L, p<0.0001) in type 2 DM patients as compared to the placebo group [23].…”
Section: Discussionsupporting
confidence: 73%